Reputable Journal Improvement Strategy Formulation on Journal of Paradigma - Dewi, Machya Astuti; Utomo, Hastho Joko Nur; Utomo, Humam Santosa (RSF Conference Series: Business, Management and Social Sciences, 2021)
Paradigma is a journal published by the Faculty of Social and Political Sciences (FISIP) University of Pembangunan Nasional Veteran Yogyakarta (UPNVY) which is intended to facilitate the publication of ideas or research results carried out by the academic community of FISIP UPNVY as well as academics/bureaucracies/practitioners outside UPNVY. The problem faced at this time is the difficulty of getting articles/writings because Jurnal of Paradigma has not been accredited by Sinta or internationally accredited. Therefore, it is necessary to formulate a strategy for achieving Jurnal of Paradigma towards Sinta accreditation. The purpose of this study is to formulate policies related to the achievement strategy of Jurnal of Paradigma towards being accredited and indexed by Sinta. This research approach is a mix-method involving qualitative and quantitative data and processed systematically using the SWOT Analysis method to get the right strategy formulation in achieving Journal of Paradigma towards Sinta accreditation. Based on the results of the analysis of internal factors and external factors, the formulation of the strategy for achieving Journal of Paradigmas is to gradually prepare Sinta accreditation and international indexation, expand Journal of Paradigma information, increase managem